The Dynamics of the Pesantren Adaptation Patterns Amid the Covid-19 Pandemic - Siti Kholifah (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
The Covid-19 pandemic has made many changes in all spheres including in education. To minimize the spread of Covid-19, the Indonesian government issued a policy for student to study at home, and since March 16, 2020 schools have implemented online learning methods. However, this cannot be applied to the education system of pesantren (Islamic boarding schools) due to limitations in access and use technology of information, as well as digital literacy. In addition economic considerations, make pesantren continue for conducting offline learning. Therefore, this study focuses on how the process of adapting pesantren in handling the Covid-19 pandemic? This study aims to determine and analyze the pattern of adaptation of pesantren in carrying out activities during the pandemic. The research was conducted at the Ar-Rohmah pesantren, Malang City as a modern pesantren that is part of ‘the pesantren tangguh’ program. By using  Robert K. Merton’s theory as an analytical tool, this research conducted an explanatory case study. Data collection techniques carried out through observation, documentation, and in-depth interviews with informants are determined purposively. The results of this study showed that at the beginning of the pandemic, the adaptation of pesantren tended to conformity pattern with longer school holidays to minimize the spread of Covid-19. At the beginning of re-entry, the Ar-Rohmah pesantren’s adaptation tended to an innovation pattern by conducting offline learning with health protocols that are not strict.  After an ustadz passed away and he was confirmed as positively infected Covid-19,  the adaptation process carried out was more conformity by conducting blended learning and all pesantren’s members more adhered to health protocols. However, in June 2021 Ar-Rohmah pesantren tend to be innovation pattern with pesantren activities that are carried out offline, which can be followed by community around the pesantren.